Bibliometric Review of Research on Startup Ecosystems with Identification of Key Authors Countries and Emerging Themes for the Period 2010–2024 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
Research on startup ecosystems has expanded rapidly over the past decade as entrepreneurship has become a key driver of innovation, technological advancement, and economic development. Despite the growing body of literature, a comprehensive understanding of the intellectual structure, collaboration patterns, and emerging themes in startup ecosystem research remains limited. This study aims to map the development of research on startup ecosystems through a bibliometric analysis of publications indexed in the Scopus database from 2010 to 2024. Using VOSviewer as the primary analytical tool, this study examines publication trends, co-authorship networks, country collaboration patterns, and keyword co-occurrence structures to identify influential authors, leading countries, and major research themes. The results show a significant growth in publications during the analyzed period, indicating increasing global academic interest in startup ecosystem studies. The co-authorship analysis reveals several collaborative clusters with a number of key scholars acting as connectors within the research network. Country collaboration analysis highlights the dominance of the United States, India, and several European countries as major contributors to the field. Furthermore, keyword analysis indicates that entrepreneurship, startup, innovation, and ecosystems form the conceptual core of the literature, while emerging topics such as artificial intelligence, blockchain, fintech, and crowdfunding reflect the growing influence of digital transformation on entrepreneurial ecosystems.